Measuring performance of conventional and islamic banks using DEA method: evidence from Malaysian banking system / Muhammad Alif Asyraf Abu Bakar - Abu Bakar, Muhammad Alif Asyraf (2020)
Malaysia is the first country in the world that has introduced dual-banking system namely conventional and Islamic banks. Banking industry in Malaysia started in 1867. As in 2017, Malaysia has a total number of 27 conventional banks and 16 Islamic banks. Measuring the performances of the banks is very important as it will lead to a good management. Efficiency and effectiveness are two main important indicators when measuring the performances of any institutions. The main objective of this study is to measure the overall performances of the banks as well as their efficiency and effectiveness score. This paper analyses the performances of conventional and Islamic banks in Malaysia which include five selected conventional banks namely CIMB Bank Bhd, Hong Leong Bank Bhd, Malayan Banking Bhd, Public Bank Bhd, and RHB Bank Bhd while another five selected Islamic banks which are Affin Islamic Bank Bhd, Bank Islam Malaysia Bhd, Bank Muamalat Malaysia Bhd, CIMB Islamic Bank Bhd, and Hong Leong Islamic Bank Bhd. This study covers years from 2014 to 2018. The researcher used a non-parametric method which is two-stage Data Envelopment Analysis (DEA) method in measuring the efficiency and effectiveness score of the banks. DEA method is a non-parametric method in operating research and economics and the best method in evaluating performances because of its characteristics as a central tendency approach. The results of this report state that conventional banks perform better than the Islamic banks. Besides, there is no bank that exhibits best practice in both stages. Finally, Public Bank Bhd and Bank Islam Malaysia Bhd are the best banks in terms of performance for conventional and Islamic banks respectively.